Design of a Current Starved Ring Oscillator Based VCO for Phase-Locked Loop - Khairun Nisa’ Minhad; Zainab Kazemi; Mamun Bin IbneReaz; Jubayer Jalil; Noorfazila Kamal (Institute of Advanced Engineering and Science, 2014)
A design of the proposed VCO was developed for PLL in radio frequency identification (RFID) application. By using current starved ring oscillator, the designed circuit is simulated using 0.18-μm CMOS process in Mentor Graphics environment. The results show that the voltage drawn is around 5V supplied at VDD, and the product of this current and voltage has approximate 105.3 mW power consumption while the VCO generates 212 MHz at 1.4 V.